Arahan Pengendalian Ruang Kawasan Perkotaan Mamasa Ditinjau Dari Kesesuaian Lahan Pertanian - Briyan Yudha Octa Pratama; Kamran Aksa; Ilham Yahya (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to determine the suitability of agricultural land in the Mamasa Urban Area and to formulate directions for spatial control in the Mamasa Urban Area, based on the suitability of agricultural land. This type of research is a mixed method research. To determine the suitability level of agricultural land in the Mamasa Urban Area using the Agricultural Land Suitability Analysis analysis tool, and to formulate spatial control directions in the Mamasa Urban Area, based on the suitability of agricultural land. The main conclusions of this study are that the suitability of agricultural land in the Mamasa Urban Area is annual crops with an area of 1538.36 ha, and the concept of controlling the suitability of agricultural land for annual crops or annual crops with an area of 1538.36 ha. According to PP No. 1 of 2011 and for plantation areas, it is directed that the conversion of paddy fields to non-rice fields is not allowed in this area.